PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Hariyati, Endah Afni; Kartikowati, Sri; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study aims to determine the effect of price and product quality on student purchase decision of xiaomi smartphone at economic education department university of riau. It’s using a quantitative descriptive approach, the populasi in the study is students using Xiaomi smartphone was as many as 40 students and the population was taken as sample (cencus sampling technique). Data collection technique using questionnaires. The analysis of data was used descriptive and linear regression. The result showed that the price of Xiaomi smartphone is in affordable category, quality of the product Xiaomi smartphone is in good category and decision purchase Xiaomi smartphone is in high category. The price and quality product have a significant effect on the decision purchase with regression Y= 2,599+0,506X1+0,397X2 and contributed decision purchase is 55,2 %.Key Words: Price, Quality Product, Purchase Decision.